Artistas mecánicos: Una mirada a la capacidad estética de máquinas y algoritmos desde la música pop y el pop art - Arriagada, Leonardo (CALLE14: revista de investigación en el campo del arte, 2021)
Despite the enormous advances that artificial intelligence (AI) and robotics have made, it is still controversial to claim that a machine can create art. Contrary to this view, I propose that behind the denial of the aesthetic capabilities of machines there is an anthropocentric bias. To illustrate this point, I take examples of the role that machines play in music and pop art. I have selected these genres because historically they have incorporated technological innovations without upheavals. Ultimately, this article takes pop music and Andy Warhol’s method of work to illuminate new points of view on the aesthetic capabilities of machines and algorithms. At the end, the thesis that machines can create art comes out strengthened.